STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN OMSET PENJUALAN PADA USAHA MIKRO KECIL MENENGAH (UMKM) KRECEK BU IPIK - Fitriani, Wiwien Ika; Subkhan, Muhammad (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2023)
In this research, it was conducted todescribe the human resource development of the Krecek bu Ipik Company, bu Ipik and to find out what strategy is suitableto develop human resources. This research using qualitative methods. Source of data used are primary and secondary data. Data collection technique is by interview and documentation. Data analysis used is SWOT analysis. From the research results can It can be concluded that the HR development strategy expected by the Krecek Bu Ipik Company is the standardization of each HR, starting from the procedures for dealing with consumers, body language and mastery of language in interacting with consumers or visitors. The strategy that has been carried out by Krecek bu Ipik Company is to hold learning classes for street vendors students, but it does not run optimally and effectively due to the tight schedule of human resources.